FAST on operational military deployment. Issue 4 (23rd March 2005) - Brooks, A J; Price, V; Simms, M
Abstract : Background and objective: Handheld ultrasound, because of its light weight, size, rugged design, and relative simplicity of use is ideal for use on operational military deployment. These machines have been used in the diagnosis of a range of traumatic conditions including abdominal, thoracic, and extremity trauma in the hospital environment, yet few data exist on their use during military operations. This paper presents experience of handheld focused assessment with sonography for trauma (FAST) on operational military deployment. Method: Over a two month period, handheld FAST was performed by a single surgeon during the circulation phase of the primary survey in trauma patients presenting to the British Military Hospital in Iraq. Results: Fifteen from casualties underwent a FAST examination. Ten were victims of blunt trauma, two had received injuries anti-personnel mines, and three had penetrating injuries from ballistic trauma. There was one positive FAST, confirmed at laparotomy as bleeding from a liver injury. Thirteen scans were negative and remained negative on repeat FAST at 6 hours. One further patient with a negative FAST underwent laparotomy because of transectory, there was no intra-abdominal blood or fluid at surgery. Conclusion: Handheld FAST is a valuable technique for investigating abdominal or thoracic bleeding in single or multiple casualty events on operational military deployment.